To the citizens of Pennsylvania : Friends and fellow-citizens, The members of the Republican Society beg leave to address you on a subject of the utmost importance to you, and to posterity . - Bache, Richard, 1737-1811
Undated broadside addressed to the citizens of Pennsylvania from the members of the Republican Society against a proposed Constitution of Pennsylvania. Of note, the group objected to the construction of the legislature into one body, as well as some judicial changes.